Multiple Cranial Nerve Palsies as the First Presentation of Sarcoidosis. (26th March 2014) - Rose, Oliver; Ahmad, Zahoor; Snow, Barry
Abstract : Sarcoidosis is a disease process which predominantly affects the lungs but can involve virtually any organ in the human body. Neurosarcoidosis is a rare manifestation which can present in a variety of ways. There is no single diagnostic test for sarcoidosis; hence, the diagnosis is based on combined clinical, laboratorial, and radiological grounds. We describe a rare case where a patient presented with dysphagia, hoarseness, hearing loss, and unsteadiness.